Comprehensive study of thoracic trauma at tertiary health care centre: a retrospective observational study - Chauhan, Ajay; Patel, Yashasvi; Ranjan, Nishant; Mehta, Fateh S. (International Surgery Journal, 2021)
Background: Thoracic injuries account for a substantial proportion of all injury-related admissions, morbidity and mortality in all tertiary health care centres. The study was conducted to do comprehensive study of chest trauma at a tertiary health care centre. Methods: In this retrospective study we included all polytrauma patients with chest trauma admitted to Geetanjali medical college and hospital, Udaipur for a period of 2 years, from January 2017 until January 2019. Clinical details of the patients were recorded from their case sheets and were analyzed with reference to their age, sex, mode of injury, type of injury, severity of injury, treatment modalities, complications and final outcome. Results: Prevalence of chest trauma was 16.61% out of total cases of polytrauma. Males were predominantly involved (79.61%). Majority were in the age group of 21-30 years. Road traffic accidents (RTA) was the most common mode of injury (68.93%). A total of 53.40% patients required inter costal tube drainage (ICTD). About 17.47% of patients developed complications during treatment in the hospital. Conclusions: Chest trauma occurs in a significant number of polytrauma patients and majority of victims are males of 21-30 years of age. Majority of these patients were treatable with simple procedures like tube thoracostomy or ICU based treatment.